Pengaruh Kepuasan Kerja Dan Stres Kerja Terhadap Turnover Intention Karyawan Pada PT. Loa Haur Energi (LHE) Di Sungai Payang Kecamatan Loa Kulu - Winda Dewi Astuti; Johansyah Johansyah; Ali Akbar (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:The purpose of this study was to determine and examine the effect of job satisfaction and stress on employee turnover intention at PT. Loa Haur Energi (LHE) in Payang River, Loa Kulu DistrictThe fact that happened at PT. Loa Haur Energi (LHE) in Sungai Payang is still a high level of employee turnover intention which is influenced by work satisfaction and stress factors. starting from January 2013 to December 2017, PT. Loa Haur Energi (LHE) that came out reached more than the standard 15% which is about 33 people from all employees. The average level of employee turnover in the last 4 (four) years at PT. Loa Haur Energi (LHE) has exceeded the tolerated standard.The sample in this study were employees of PT. Loa Haur Energy (LHE) in the Payang River as many as 65 people. The sampling technique was by using probality sampling. the analytical tool used is the multiple regression equation with the hypothesis test used by the F and t tests.From the ANOVA test or F test, the F count obtained is 27.653, while the F table value obtained a value of 2.75 this means that (Fcount 27.653> Ftable 2.75) so that it can be said that job satisfaction and job stress variables are jointly able showed a significant effect on employee turnover intention at PT. Loa Haur Energy (LHE) in Payang River, Loa Kulu District. This is reinforced by the results of the number R is 0.687. This is that the correlation between the variable job satisfaction and job stress on employee turnover intention is a strong relationship. The adjusted R square figure is 0.454 which means that 45.4% of employee turnover intention can be explained or influenced by the variables of job satisfaction and job stress while the remaining 54.6% of employee turnover intention at PT. Loa Haur Energi (LHE) in Sungai Payang, Loa Kulu District by other causes such as compensation, work atmosphere, commitment and leadership. So the first hypothesis is accepted.Based on the correlation table shows that the variable job satisfaction has the most dominant influence on employee turnover intention at PT. Loa Haur Energy (LHE) in Payang River, Loa Kulu District, which is 0.627 or 62.7%, followed by work stress variable of 0.437 or 43.7%. So it can be concluded that at PT. Loa Haur Energi (LHE) in Payang River, Loa Kulu Subdistrict, job satisfaction variable has a dominant effect on employee turnover intention. So the second hypothesis is acceptedKeywords: job satisfaction, job stress, turnover intention